2021
DOI: 10.3389/fcell.2020.611354
|View full text |Cite
|
Sign up to set email alerts
|

Prkaa1 Metabolically Regulates Monocyte/Macrophage Recruitment and Viability in Diet-Induced Murine Metabolic Disorders

Abstract: Myeloid cells, including monocytes/macrophages, primarily rely on glucose and lipid metabolism to provide the energy and metabolites needed for their functions and survival. AMP-activated protein kinase (AMPK, its gene is PRKA for human, Prka for rodent) is a key metabolic sensor that regulates many metabolic pathways. We studied recruitment and viability of Prkaa1-deficient myeloid cells in mice and the phenotype of these mice in the context of cardio-metabolic diseases. We found that the deficiency of Prkaa1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Deletion of the AMPK β1 subunit from the hematopoietic compartment worsens liver inflammation and increases hepatic immune infiltration in male mice fed an HFD ( 23 ). In contrast, LysM-mediated deletion of the AMPK α1 subunit was shown to diminish monocyte recruitment and macrophage infiltration under high-fat feeding conditions, which was accompanied by worsened steatosis and insulin resistance in a mix of male and female mice ( 33 ). Our data suggest that removing AMPK signaling in myeloid cells has little consequence on the degree of steatosis or inflammation, but significantly impacted the level of fibrosis in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of the AMPK β1 subunit from the hematopoietic compartment worsens liver inflammation and increases hepatic immune infiltration in male mice fed an HFD ( 23 ). In contrast, LysM-mediated deletion of the AMPK α1 subunit was shown to diminish monocyte recruitment and macrophage infiltration under high-fat feeding conditions, which was accompanied by worsened steatosis and insulin resistance in a mix of male and female mice ( 33 ). Our data suggest that removing AMPK signaling in myeloid cells has little consequence on the degree of steatosis or inflammation, but significantly impacted the level of fibrosis in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the severity of this diet coupled with confounding effects (such as weight loss) led to the development of a diet that is deficient for choline and with restricted levels of methionine in conjunction with high-fat content (CDAHFD), which has been shown to augment NASH progression without affecting weight ( 27 ). Given the role of myeloid AMPK signaling in modulating macrophage polarization in the context of adipose tissue inflammation ( 23 ), skeletal muscle regeneration ( 28 , 29 ) and atherosclerosis ( 30 , 31 , 32 , 33 ), we sought to clarify if AMPK signaling in resident and infiltrating liver macrophages was protective in a CDAHFD-induced NASH model. In male and female mice, CDAHFD-induced significant fibrosis and worsened circulating levels of liver injury markers.…”
mentioning
confidence: 99%
“…The remaining suspension cells were collected and reseeded into a 6-well plate at a density of 2 x 10 6 cells/mL. Cells were cultured in RPMI 1640 medium (SH30027.01, Cytiva, Marlborough, MA, USA) supplemented with 10% FBS (F4135, Sigma-Aldrich, St. Louis, MO, USA), 10 ng/mL MCSF (315-02, PeproTech, Cranbury, NJ, USA) and 1% Antibiotic-Antimycotic (15240062, Thermo Scientific, Grand Island, NY, USA) in a humidified incubator with 5% CO2 at 37°C for 7 days to induce macrophage differentiation as described before ( 45 ). After 7 days, the differentiated cells were cultured in RPMI 1640 medium supplemented with 1% FBS, 1% Antibiotic-Antimycotic, and 10 ng/mL MCSF.…”
Section: Methodsmentioning
confidence: 99%
“…In adipose tissue, macrophage exposure to the saturated fatty acid palmitate triggers an upregulation of HIF-1α that increases glycolysis and ultimately leads to IL-1β production (117). Death of pseudohypoxic adipocytes initiates macrophage pro-inflammatory translation, and atherosclerotic injury associated with abnormal lipid metabolism also shifts macrophages from the M2 to the M1 type (118). These studies suggested that when macrophages are in adipose tissue, the hypoxic environment induces macrophage glycolysis and polarization toward the M1 type, which also provides ideas for inflammation therapy (117,118).…”
Section: Effects Of Altered Levels Of Myeloid-derived Suppressor Cell...mentioning
confidence: 99%